Weight Gain During Pregnancy To Childbirth - uli laili; Ratna Ariesta dwi Andriani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2020)
Increased energy and nutrients are needed for fetal growth and development, increase in the size of the uterine organs, as well as changes in the composition and metabolism of the mother's body. The nutritional status of pregnant women can be seen through several factors including the adjusted body mass index (BMI) of the mother before pregnancy which will affect how much the ideal increase in pregnancy during pregnancy, including the size of the LLA (Upper Arm Circumference) to achieve an ideal state. It aims to prevent weight gain that is too much or too little for pregnant women who will also affect the birth process and the condition of the fetus being born. The purpose of this study was to analyze the relationship between maternal weight gain during pregnancy and childbirth. The research method used is quantitative, with cross sectional approach. The study was conducted at the Jagir Community Health Center in Surabaya, with a sample of 80 people. Data obtained using SPSS with chi square test. The results showed there was a relationship between maternal weight gain during pregnancy which was seen based on body mass index (BMI) with the labor process that took place. In the implementation of midwifery care for pregnant women nutritional status monitoring and weight gain are monitored since the beginning of pregnancy so that labor takes place smoothly